Influence of l-carnosine on pro-antioxidant status in elite kayakers and canoeists - Slowinska-Lisowska, M.; Zembron-Lacny, A.; Rynkiewicz, M.; Rynkiewicz, T.; Kopec, W. (Acta Physiologica Hungarica, 2014)
Carnosine is a dipeptide formed from the amino acids ß-alanine and histidine and found in large amounts in the brain and muscle, especially fast twitch muscle. Carnosine has an antioxidant role and accounts for about 10% of the muscle's ability to buffer the H+ ions produced by high intensity exercise. Due to the interesting role of carnosine, the aim of the study was observe the effects of carnosine intake on pro-antioxidant status in highly trained athletes exposed to intense exercise.Fourteen male athletes from the Polish national kayak and canoe teams participated in placebo-controlled and cross-over study. The athletes were supplemented with 4 g/d carnosine for 14 days. Blood samples were collected before and 30 min, 24 h and 48 h after 2000 m exercise trial. In blood, hydrogen peroxide (H2O2), nitric oxide (NO), markers of RO/NS activity 8-isoprostanes and 3-nitrotyrosine, total (GSHt) and oxidised glutathione (GSSG), antioxidant status (APO) and superoxide dismutase (SOD) were determined. There were not observed statistically significant differences in exercise-induced changes in H2O2 and NO concentrations and SOD activity after carnosine intake. However, carnosine prevented an increase in 8-isoprostanes, 3-nitrotyrosine and GSSG concentrations as well as elevated redox status (GSHt-2GSSG)/GSSG at post-exercise period.Although, oral supplementation with 4 g carnosine did not affect RO/NS generation, it significantly attenuated exercise-induced glutathione loss, reduced oxidation/nitration markers concentration and SOD activity. These results suggest that carnosine could provide antioxidative protection for highly trained athletes.